Guardians of the tradition and slaves of routine: a history of the professional field of secondary school teaching. - Cuesta Fernández, Raimundo; Mainer Baqué, Juan (Historia y Memoria de la Educación, 2015)
This article deals with the formation, development, crisis and decline of the professional field of secondary school teaching. In order to examine the origins of this socio-cultural institution we must resort to a quantitative study as well as a study of the evolution of regulations governing the field. More importantly, though, we must delve into the ethos of its many components - its ideological codes and norms, its unwritten rules - that eventually led to the consolidation of a remarkably robust and abiding professional standard. The article also provides an up-to-date and revealing overview of the state of research on the subject.